2013
DOI: 10.1038/nrm3721
|View full text |Cite
|
Sign up to set email alerts
|

Adult intestinal stem cells: critical drivers of epithelial homeostasis and regeneration

Abstract: Small populations of adult stem cells are responsible for the remarkable ability of the epithelial lining of the intestine to be efficiently renewed and repaired throughout life. The recent discovery of specific markers for these stem cells, together with the development of new technologies to track endogenous stem cell activity in vivo and to exploit their ability to generate new epithelia ex vivo, has greatly improved our understanding of stem cell-driven homeostasis, regeneration and cancer in the intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
990
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,042 publications
(1,054 citation statements)
references
References 121 publications
15
990
1
15
Order By: Relevance
“…As the ISC compartment is maintained by Wnt and Notch signals, 1 we tested the effects of the ligands Wnt3a and Jagged1, which are known to activate the Wnt and Notch pathways in organotypic culture. 33 We found that Wnt3a, but not ); GDC: GDC0941 500 nM).…”
Section: Above)mentioning
confidence: 99%
See 2 more Smart Citations
“…As the ISC compartment is maintained by Wnt and Notch signals, 1 we tested the effects of the ligands Wnt3a and Jagged1, which are known to activate the Wnt and Notch pathways in organotypic culture. 33 We found that Wnt3a, but not ); GDC: GDC0941 500 nM).…”
Section: Above)mentioning
confidence: 99%
“…These in turn differentiate into enterocytes and secretory cell types. 1 Cellular hierarchies are gradually modified during intestinal tumor initiation and progression by mutations in signaling pathways controlling homeostasis. Consequently, colon cancers can therefore exhibit gene activity characteristic for different intestinal cell types and colon cancer subtypes defined by such expression patterns differ in their therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that, as in the differentiation process, the transcriptional response of intestinal cells to the microbiota is regulated mainly by the differential binding of SDTFs, independently of changes in chromatin accessibility. One hypothesis is that in cells with such a short lifespan of 3-5 days [50], it may be more effective to have inducible TFs operating in an already accessible, and therefore permissive, chromatin landscape to respond to an insult. Comprehensive experimentation in other cell types that have also a relatively medium to high turnover and are equally capable of mounting an innate response such as lung epithelial cells [51] or skin keratinocytes [52] may allow us to derive a more general picture.…”
Section: H3k27ac H3k4me1mentioning
confidence: 99%
“…On the other hand, regenerative events in more complex organisms, such as regeneration of a vertebrate limb, heart, or retina, depends on cells with limited lineage differentiation potential, which often arise from dormant or dedifferentiated cells (reviewed by Jopling et al, 2011). Humans continuously repair their intestinal epithelium through use of small reservoirs of intestinal stem cells that continuously proliferate and differentiate into a handful of epithelial cell types (reviewed by Barker, 2014). These cells, however, would be expected to fail at restoring damaged tissue outside the intestine under normal conditions, due to their limited potency.…”
Section: Labib Rouhana and Junichi Tasakimentioning
confidence: 99%